Compressive Sensing Based Algorithms for Electronic Defence - Mishra, Amit Kumar; Verster, Ryno Strauss; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book details some of the major developments in the implementation of compressive sensing in radio applications for electronic defense and warfare communication use. It provides a comprehensive background to the subject and at the same time describes some novel algorithms. It also investigates application value and performance-related parameters of compressive sensing in scenarios such as direction finding, spectrum monitoring, detection, and classification.
Introduction -- Electronic Warfare Communication Systems -- Compressive Sensing applied to Electronic Support tasks.
Keywords: Signal processing; Computers, Special purpose; Security systems; Telecommunication; Signal, Speech and Image Processing; Special Purpose and Application-Based Systems; Security Science and Technology; Communications Engineering, Networks